First records of the Oriental Eurhadina (Singhardina) robusta species group from China with descriptions of five new species (Hemiptera: Cicadellidae: Typhlocybinae) - Zhou, Juan; Zhang, Yalin; Huang, Min (Zootaxa, 2021)
Five new species, Eurhadina (Singhardina) dissimilis, E. (S.) flatilis, E. (S.) fumosa, E. (S.) furca and E. (S.) immatura spp. nov., and two new records, E. (S.) krispinilla rec. nov., E. (S.) pookiewica rec. nov. of the leafhopper subgenus Eurhadina (Singhardina) Mahmood from China are described and illustrated and a key to all members of the E. (S.) robusta species group is provided.